The Insuline Analogues - Garrido Carrasco, Elizabeth (2001)
Insulin analogues are a new pharmaceutical family, designed to overcome deficiencies that still exist with the rDNA insulin. There are rapid-acting insulin analogues such as lispro insulin and insulin aspart. They avoid postprandial and nocturnal hypoglycemia. There are also intermediate-acting insulin analogues like NPL and Mix 25 (a mixture between NPL and lispro), which join the neutral protamine insulin length of action and the fast onset of the rapid-acting analogue lispro. Finally, there is a long-acting analog: glargine, showing a 24-hours action and a peakless profile. In the near future we will have acylated analogues, to get better insulin levels into the liver. This large group of novel patterns of insulin activity provides new options in the treatment of diabetic patients, heading for lower complication risks. The main characteristics, chemical properties and therapeutic applications of each analog were reviewed, because all this drug family is with us nowadays.